Two axis solar tracker based on solar maps, controlled by a low-power microcontroller - Duarte, Francisco (2019)
Submitted by GASPAR (dinis@ubi.pt) on 2019-11-20T14:29:09Z No. of bitstreams: 1 Two-axis-solar-tracker-based-on-solar-maps-controlled-by-a-lowpower-microcontroller.pdf: 800011 bytes, checksum: a6e6f5c33ecd21f431fa1446d84e2344 (MD5)